Investigate the World because of the Empirical Sensation of Reality in All Its Universal Completeness and Manifestyle - Zhangozha, Rustem (HISTORY, ARCHAEOLOGY, ETHNOLOGY; No I (2018), 2019)
In this article the overview of turbulent processes, in which complex configurations of different ethnocultural discourses is discussed. Dramatic situation is not in parity and absence of actor's consensus of this process, which summons painful reaction of the participants of these contacts.